(untitled) (South Asian Journal of Agriculture, 2022)
Litchi is a popular summer fruit in Bangladesh and the production of litchi is increasing day by day. However, the production procedure of litchi is not a problem free venture. The Meherpur district of Bangladesh is a suitable place for commercial cultivation of litchi. Thus, the present study was conducted to determine the status of litchi cultivation and to identify the problems confronted by the litchi growers of Meherpur Sadar and Mujibnagar upazila of Meherpur district, Bangladesh. Data were collected through a pre-tested interview schedule from 60 respondents selected by accidental sampling during May to June, 2019. Majority of the respondents (58.3%) belong to early initiation category of litchi cultivation (during 1996 to 2012) with early (3-5 years) fruit collection (51.7%). Most of the respondents (80.0%) allotted small area (up to 0.5 ha) of land for litchi cultivation; and 41.7% used low extent for litchi cultivation i.e., 40% of the potential area; and all the respondents belonged to continuous adoption category. Most of the respondents (80.0%) cultivate Bombai variety and 73.3% had moderate number (86-135) of plants in their orchard; and about one-third of the respondents (30.0%) maintain a spacing of 4.65m×6.20m in their litchi orchard. Two-fifth (40.0%) of the respondents harvested a moderate yield (1,00,001-2,00,000 fruits ha-1), however, most of the respondents (81.67%) argued that they get low price (up to 1,25,000 BDT ha-1) from their litchi orchards . Majority of the respondents (68.33%) reported that litchi fruit and shoot borer infest their orchard while the orchards of 45% respondents were infested by fruit rot disease. Majority of the respondents (68.3%) confronted medium extent of problems followed by low (18.3%) and high (13.4%) extent of problems. The most severe problems were lack of training on litchi cultivation and low shelf life of litchi as reported by all (100%) of the respondents. Among eleven selected socioeconomic characteristics of the respondents’ only farm size, annual income, cosmopolitanism and knowledge on litchi cultivation showed significant negative relationship with their problem confrontation. It might be concluded that proper, adequate and timely extension activities would minimize the extent of problems in litchi cultivation to ensure sustained higher yield in Bangladesh. South Asian J. Agric., 8(1&2): 20-28